Microplastic: pollution issue and seafood security - Khusnul Yaqin (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2021)
At the first time, plastic materials were produced to facilitate various activities of human life. Plastic materials that are flexible and durable have been used by humans to meet various needs to support their daily activities. Starting from human activities from waking up to going back to sleep, nowadays it cannot be separated from the use of plastic materials. This then makes humans "addicted" to plastic materials. It is as if human life cannot be separated from the use of plastic materials. Various research results in the field of pollution both on land and the sea, plastic materials that are not managed properly can contaminate human life, either directly or indirectly, to food sources, especially food from the sea.